EVALUASI SEBARAN LOKASI DAN TINGKAT KEPUASAN KONSUMEN STASIUN PENGISIAN BAHAN BAKAR UMUM BERBASIS APLIKASI SISTEM INFORMASI GEOGRAFIS DI KABUPATEN DEMAK - Erna Puji Astutik; Ananto Aji; Saptono Putro (Geo-Image, 2017)
Business development of Gas Station increases every year. This is in line with the level of consumption of oil so that it affects what is required by consumers. Therefore, it takes a thought to overcome it. The population is SPBU in Demak Regency as many as 20 pieces and all gas stations used as sample. Samples for customer satisfaction use incidental sampling technique. The research variables are (1) Variable distribution of gas stations location: number, distance, and location of gas station, number and type of motor vehicle, traffic density; (2) Variable levels of customer satisfaction: tangible, empathy, reliability, assurance, and responsiveness. The research analyzes used Geographic Information System analysis, nearest neighbor analysis, and quantitative descriptive. The results showed that the distribution pattern of gas stations has a uniformly distributed pattern; The location suitability class of 20 gas stations is included in the appropriate criteria (S2) with the calculation of 70%; And customer satisfaction to the service provided from the SPBU of 4,991 which, when included in the assumption of research calculation included in the Good category. With the results of these shows that the distribution of location and level of consumer satisfaction SPBU in Demak Regency region including good criteria.